Clinical features and evolution of juvenile myasthenia gravis in a French cohort. Issue 4 (11th October 2017) - Barraud, Coline; Desguerre, Isabelle; Barnerias, Christine; Gitiaux, Cyril; Boulay, Christophe; Chabrol, Brigitte
ABSTRACT: Introduction: In this study we determined the clinical, paraclinical, and treatment‐related features of juvenile myasthenia gravis (JMG) as well as the clinical course in a cohort of French children. Methods: We conducted a retrospective study of 40 patients with JMG at 2 French pediatric neurology departments from April 2004 to April 2014. Results: Among the patients, 70% had generalized JMG, 52% had positive acetylcholine receptor antibodies, 8% had muscle‐specific kinase antibodies, and 40% were seronegative. Treatment with acetylcholinesterase inhibitors was effective and sufficient in 47% of patients. The 6 patients with generalized JMG treated with rituximab and/or immunoadsorption showed improvement. Thirty percent of the patients required hospitalization in an intensive care unit during follow‐up (mean 4.7 years). Remission without treatment occurred in 18% of patients. Discussion: As with adults, JMG has high morbidity, particularly among children with generalized symptoms, and rituximab should be considered early in the course of the disease as a second‐line treatment. Muscle Nerve 57 : 603–609, 2018